Kualitas Bakteri Udara Ruang Operasi Rumah Sakit di Wilayah Kota Jayapura - Sahli, Indra Taufik; Kurniawan, Fajar Bakti; Setiani, Dwi; Asrianto, Asrianto; Hartati, Risda (Health Information : Jurnal Penelitian, 2021)
Indoor air quality is a problem that needs attention because it will affect human health. Bacteria found in hospital room air are one of the causes of infectious diseases called nosocomial infections. This research is a descriptive study with a laboratory observational approach to determine the quality of airborne bacteria in the operating room of Abepura Hospital and Dian Harapan Hospital in Jayapura city. Determination of the number of samples using the total sampling method, which is taking all samples of the operating room at Abepura Hospital and Dian Harapan Hospital. Each room is taken once, namely in the morning with 2 sampling points. The stages of this research were started by placing a petri dish containing PCA media and counting the total number of microorganisms in the operating room at Abepura Hospital and Dian Harapan Hospital. The results of research at Abepura Hospital, the microorganism number index in OK 1 room was 13 CFU/M³, OK2 was 4 CFU/M³, OK 3 was 1.3 CFU/M³ and OK room 4 was 0 CFU/M3. The results of research at Dian Harapan Hospital, the microorganism number index in the OK 1 room was 4 CFU / M³, OK2 = 0 CFU / M3, OK 3 was 6.5 CFU / M³ and the OK 4 room was 11.7 CFU/M3. The conclusion is that all operating rooms both in Abepura Hospital and Dian Harapan Hospital still meet the requirements by the Permenkes no. 7 of 2019.